Dyplomacja naukowa w cieniu żelaznej kurtyny. Węgierskie religioznawstwo w latach 1950–1970 - Kusiak, Paweł (Humaniora. Czasopismo Internetowe, 2024)
Valerio Severino, Documenting the History of Religions in the Hungarian Academy of Sciences (1950–1970). Letters, Reports and Requests across the Iron Curtain, Brill, Leiden–Boston 2021, ss. 174.